Dealing with Key Terms in Risk Analysis and Phenomenon of Uncertainty in this Process - Holla, Katarina (Communications - Scientific letters of the University of Zilina, 2007)
Unifying key terms in crisis management is one of the main vague field when performing risk analysis. Differences between terms and their definitions should eventuate into problems with communication in this area. I will mention a causal relationship between danger, treat and risk and I will try to integrate them into the surrounding of technological processes. In the next paragraph I will be dealing with risk analysis which should be characterized as a systematic use of available information to determine how often specified events may occur and the magnitude of their likely consequences. Therefore the wide range of uncertainty will occur when performing risk analysis. The main sources of uncertainty were described in projects made by Joint Research Centre as a part of whole assurance project, known as benchmark studies made for two chemical and one nuclear power plants.